Vitamin D and focal brain atrophy in PD with non-dementia: a VBM study - Xu, Yingying; Wang, Erlei; Zhang, Qilin; Liu, Jing; Luo, Weifeng (Frontiers in Human Neuroscience, 2024)
BackgroundThe status of vitamin D has been proposed to have an impact on cognition. Gray matter volume (GMV) is a potential marker of cognitive function. We investigated whether lower serum 25-hydroxyvitamin D level was associated with reduced cerebral GMV in Parkinson’s disease with non-dementia (PDND) patients.MethodsBaseline neuropsychiatric performance and serum 25-hydroxyvitamin D levels were examined in 24 PDND patients and 24 healthy controls (HCs). A set of cognitive scales were used to evaluate the cognition. Voxel-based morphometry (VBM) was performed to calculate each PDND patient’s GMV, based on structural magnetic resonance imaging data. Associations between serum 25-hydroxyvitamin D levels, cognition, and GMV were evaluated.ResultsThe serum 25-hydroxyvitamin D levels of the PDND group were significantly lower than those of the HC group. The simple linear regression analyses between serum 25-hydroxyvitamin D levels and the scores of subtests that analyzed cognitive function showed that serum 25-hydroxyvitamin D levels were negatively correlated with Trail Making Test-A scores and positively correlated with Symbol Digit Modalities Test and Auditory Verbal Learning Test scores. Multiple regression analyses revealed a positive correlation between the right fusiform gyrus GMV and serum 25-hydroxyvitamin D levels.ConclusionWe hypothesized that the lower serum 25-hydroxyvitamin D level in patients with PDND might affect auditory word learning and spatial cognition ability by reducing the gray matter volume of the right fusiform gyrus, thereby leading to deterioration of semantic understanding and memory function.